3-Dimensional Quantification of Composite Pleural Plaque Volume in Patients Exposed to Asbestos Using High-resolution Computed Tomography: A Validation Study. Issue 5 (September 2019) - Dournes, Gael; Dubois, Adrian; Benlala, Ilyes; Lacourt, Aude; Paris, Christophe; Gislard, Antoine; Clin, Benedicte; Pairon, Jean-Claude; Baldacci, Fabien; Laurent, François
Abstract : Rationale: As pleural plaque has been reported as a risk factor in the occurrence of lung cancer and mesothelioma, a reproducible and precise method of measurement of pleural plaque volume (PPV) is needed to further describe these relationships. The aim of the study was to assess the reproducibility of a 3-dimensional computed tomography (3D-CT) volumetric analysis of PPV in patients with occupational exposure to asbestos. Material and Methods: A total of 28 patients were retrospectively randomly selected from the multicenter APEXS (Asbestos Post Exposure Survey) study, which was held between 2003 and 2005. All patients underwent a 3D-CT scan. Two readers specialized in chest radiology completed the 3D semiautomated quantification of lung volume using dedicated software. They also had to categorize the visual extent of pleural plaque in terms of thickness and circumference. Reproducibility of the continuous PPV variable was assessed using the intraclass correlation coefficient (ICC) and Bland-Altman analysis. Reproducibility of categorical variables was assessed using the κ test. Results: Intraobserver reproducibility of PPV was almost perfect (ICC=0.98 [95% interval: 0.97-0.99]), and interobserver reproducibility was very good (ICC=0.93 [0.88-0.97]). At Bland-Altman analysis, the mean differences were 0.1 (limit of agreement: −11.0 to 11.2) and 3.7 cc 3 (−17.8 to 25.2), respectively. Visual analysis of both plaque in terms of thickness and circumference were fair to moderate, with κ values ranging from 0.30 to 0.60. Conclusions: 3D semiautomatic quantification of PPV is feasible and reproducible using CT in patients with occupational exposure to asbestos. PPV measurement may be useful to correlate with other asbestos-related disease outcomes and prognosis. Abstract : Supplemental Digital Content is available in the text.